Traces of Islam in Minority Lands: The Historical Journey of Muslim Civilization in the Netherlands - Afrinaldi, Rori; Darmawan, Budi; Anggraini, Riri; Wijaya, Iqra Pandu; Hasibuan, Nur Anisah (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This article explores the history and dynamics of the Dutch Muslim minority community in relation to the broader context of Islam. The introduction of Islam into the Netherlands can be traced back to various historical events and waves of migration. Initially, Arab traders played a pivotal role in introducing Islam to the region through their commercial activities. Subsequently, the Ottoman Turks contributed to the spread of Islam in the Netherlands, particularly during periods of trade and diplomacy. However, one of the most significant chapters in this narrative unfolded after World War II, when a new wave of immigrants sought asylum and refuge in the Netherlands. These immigrants brought with them their diverse cultural backgrounds and religious beliefs, including Islam. This era marked a transformative period in Dutch society, shaping its multicultural landscape and religious composition. It's noteworthy that the Netherlands is recognized as one of the most secular countries in Europe. This secular ethos is enshrined in the country's governance and policies, which prioritize individual freedom of religion and belief. Unlike some other nations, the Dutch state upholds the principle of religious freedom, allowing its citizens to choose their faith without coercion or compulsion. In conducting this study, the literature research method was employed. This approach involves a comprehensive review and analysis of various scholarly works, publications, and primary sources available in libraries. The researcher leverages a wide array of resources, such as books, academic journals, newspapers, and archival materials, to gain insights into the historical context and contemporary dynamics of Islam and its practitioners within the Dutch context.